2019
DOI: 10.1007/s00259-018-4252-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in [11C]ABP688 binding: a positron emission tomography study of mGlu5 receptors

Abstract: Purpose The purpose of this study was to assess, in a large sample of healthy young adults, sex differences in the binding potential of [ 11 C]ABP688, a positron emission tomography (PET) tracer selective for the metabotropic glutamate type 5 (mGlu5) receptor. Methods High resolution [ 11 C]ABP688 PET scans were acquired in 74 healthy volunteers (25 male, 49 female, mean age 20 ± 3.0). Mean binding potential (BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…3D to G). As we observed previously in a larger sample, 38 the overall BP ND was higher in men than women (t 15 = −2.7, p = 0.015) by an average of 26% across re gions (Appendix 1, Figure S4). A single day 1 scan in each of the Amph and placebo groups was excluded because of low injected activity and high injected mass, respectively (Appen dix 1), resulting in a final sample size for primary PET com parisons of 9 Amphtreated participants and 8 placebo par ticipants.…”
Section: Availability Of Mglu5 In Humanssupporting
confidence: 79%
“…3D to G). As we observed previously in a larger sample, 38 the overall BP ND was higher in men than women (t 15 = −2.7, p = 0.015) by an average of 26% across re gions (Appendix 1, Figure S4). A single day 1 scan in each of the Amph and placebo groups was excluded because of low injected activity and high injected mass, respectively (Appen dix 1), resulting in a final sample size for primary PET com parisons of 9 Amphtreated participants and 8 placebo par ticipants.…”
Section: Availability Of Mglu5 In Humanssupporting
confidence: 79%
“…Indeed, despite the presence of mGlu5 receptors in the cerebellum, only a negligible fraction specifically binds to the radiotracer [ 58 ], minimizing the likelihood of a bias or difference in cerebellar uptake between our groups. Instead, we recently documented that much of the variability in [ 11 C]ABP688 BP ND [ 59 ] reflects effects of time of day [ 60 ], (Z)- isomer content in the synthesized batch of tracer [ 53 ], and sex [ 54 ]. All three factors were controlled for in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For all ANCOVAs and t -tests, sex, isomer ratio, AUDIT scores, tobacco smoking status and drug use (other than cannabis) were included as covariates. Each of these factors is associated with differences in [ 11 C]ABP688 BP ND [ 22 24 , 26 , 53 , 54 ]. Greenhouse-Geisser corrections were applied when the assumption of sphericity was violated ( p < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies from the same research group showed that the whole brain [ 11 C]ABP688 ( 82 ) BP ND was 17% higher in men than in women, irrespective of the menstrual phase or hormonal contraceptive use of the female subjects [ 178 ]. Another [ 11 C]ABP688 ( 82 ) study in 18 men and 13 women did not show any significant gender difference, and only a hint of a decline in BP ND as a function of age [ 179 ].…”
Section: Glutamate Receptorsmentioning
confidence: 99%